2012
DOI: 10.3928/01477447-20120919-57
|View full text |Cite
|
Sign up to set email alerts
|

Femur Positioning in Navigated Total Knee Arthroplasty

Abstract: Navigated total knee arthroplasty (TKA) results in better restoration of neutral mechanical axis than does the conventional technique. Nevertheless, coronal malalignment has not been eliminated. It is yet unknown whether errors in implant positioning occur more on the femoral side, more on the tibial side, or equally on both sides. The hypothesis of this study was that a predominance of coronal component malalignment exists on the tibial side in navigated tibia-first TKA.Fifty-seven consecutive navigated (Orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Reliable use of the gap-balancing technique with a sufficiently accurate tibial cut is therefore ensured. Femoral rotation is more accurate if it has already been balanced in extension, and avoids secondary rotational malalignment of the femoral component due to a varus or valgus malalignment of the tibial component [43,44]. Raising the joint line by up to 5 mm is then possible without having a detrimental effect [40,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Reliable use of the gap-balancing technique with a sufficiently accurate tibial cut is therefore ensured. Femoral rotation is more accurate if it has already been balanced in extension, and avoids secondary rotational malalignment of the femoral component due to a varus or valgus malalignment of the tibial component [43,44]. Raising the joint line by up to 5 mm is then possible without having a detrimental effect [40,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…However, a highly accurate proximal tibial cut is required for the GB technique because initial tibial alignment errors will be carried through to all subsequent cuts [ 26 ]. There is evidence that secondary rotational malalignment of the femoral component can be caused by malalignment of the tibial component in the coronal plane [ 27 ]. We previously presented a study that demonstrated that the use of patient-specific instrumentation (PSI) may be advantageous to achieve optimal component positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Innovations including navigation and patientspecific instrumentation have been introduced to theoretically improve the accuracy of alignment obtained with conventional instrumentation [11,14,35,40]. The evaluation of navigation has shown that, although it is possible to improve accuracy in the coronal plane [12,23,40], it is not as effective in improving accuracy of rotation or tibial slope [11,12,17,31].…”
Section: Introductionmentioning
confidence: 99%